2015
DOI: 10.3758/s13415-015-0362-7
|View full text |Cite
|
Sign up to set email alerts
|

Fairness influences early signatures of reward-related neural processing

Abstract: Many humans exhibit a strong preference for fairness during decision-making. Although there is evidence that social factors influence reward-related and affective neural processing, it is unclear if this effect is mediated by compulsory outcome evaluation processes or results from slower deliberate cognition. Here we show that the feedback-related negativity (FRN) and late positive potential (LPP), two signatures of early hedonic processing, are modulated by the fairness of rewards during a passive rating task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Because increases in spectral power in the theta frequency range (4–8 Hz) typically accompany the FRN [63], we analyzed theta power at the anterior ROI within the 200–300 ms that followed pitch onsets at the three event positions [7,56,72]. To allow for the specification of a temporal baseline period as well as a temporal buffer, with the purpose of preventing edge artifacts within the 100-ms epoch of interest, time-frequency decompositions were calculated for each participant in a −1000 to +1000 ms time window centered on pitch onsets [73].…”
Section: Methodsmentioning
confidence: 99%
“…Because increases in spectral power in the theta frequency range (4–8 Hz) typically accompany the FRN [63], we analyzed theta power at the anterior ROI within the 200–300 ms that followed pitch onsets at the three event positions [7,56,72]. To allow for the specification of a temporal baseline period as well as a temporal buffer, with the purpose of preventing edge artifacts within the 100-ms epoch of interest, time-frequency decompositions were calculated for each participant in a −1000 to +1000 ms time window centered on pitch onsets [73].…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that the FRN occurred slightly later during the present study than is typically observed. We attributed this late arrival to a different complexity of our stimulus compared to other experiments (Massi and Luhmann, 2015). The third component is a large positive component lasting from 420 ms to 700 ms, which we identified as the LPC.…”
Section: Resultsmentioning
confidence: 81%
“…Studies primarily concentrated on changes of the Feedback-Related Negativity (FRN; also referred to as the medial frontal negativity), an ERP associated with feedback processing (Boksem and De Cremer, 2010; Wu et al, 2012; Alexopoulos et al, 2013; Qu et al, 2013; Ma et al, 2015). This component occurs in an extended latency range associated with the complexity of the stimulus (Massi and Luhmann, 2015), approximately 200–400 ms after stimulus onset (Massi and Luhmann, 2015; Sambrook and Goslin, 2015). Its amplitude increases whenever offers are judged as unfair (Osinsky et al, 2014; Kaltwasser et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…P3 activation in social dilemmas includes the chicken game 120,121 , prisoner's dilemma 26,27 , dictator 122 , and ultimatum games [123][124][125][126][127] . Our data shows that the P3 is modulated by the co-player's choice to cooperate, consistent with increased P3 levels for positive reward.…”
Section: Electrophysiological Responses To Presented Feedbackmentioning
confidence: 99%